Fabrication of drug-eluting polycaprolactone and chitosan blend microfibers for topical drug delivery applications - Gizaw, Mulugeta; Bani Mustafa, Diala; Chou, Shih-Feng (Frontiers in Materials, 2023)
Chronic and non-healing wounds show delayed and incomplete healing process, which expose the patients to a high risk of infection. These types of wounds require frequent change of dressing, which is a burden on the patients. In addition, ideal dressing needs to meet the requirements in minimizing microbial infiltration and growth while balancing moisture and exchanging oxygen with outside environment. To overcome the challenge in frequent change of dressing and meet the design requirements, current researches have focused on the development of electrospun fibers with incorporation of small molecule drugs for sustained release purpose. In this study, electrospinning was performed to fabricate blend fibers consisting of 15 wt% of polycaprolactone (PCL) and 4 wt% of chitosan (CS) at various blend ratios with the incorporation of a model small molecule drug, acetylsalicylic acid (ASA). Results showed that fibers became more hydrophilic when increasing CS concentration from 0% to 60% in PCL/CS blank fibers. Increasing CS concentration decreased fiber diameter resulting in the decrease of fiber mechanical properties. Furthermore, the addition of 10% w/w ASA also made the fibers more hydrophilic and further decreased the fiber diameter. There were no linear relationships between CS concentrations and fiber mechanical properties in the drug-loaded samples, which indicated some level of drug-polymer interactions. Fiber mechanical properties and drug release rates were two major aspects indicative of strong and/or weak drug-polymer interactions. In vitro drug release in PBS buffer solution showed a burst profile of ASA (30%) up to 2 h followed by a zero-order release rate up to 2 days.